Associação entre exposição a agrotóxicos, depressão e desesperança na população do município de Anahy/PR - Machado, Meiriane Bürger (2018)
The consumption of pesticide on a large scale generates problems for biodiversity and for human health, such as acute and chronic intoxications. These intoxications may be associated with several diseases, such as mental disorders, suicide attempts and suicide, which indicates their relevance to public health. The cross - sectional, descriptive, quantitative study aimed to identify the association between exposure to pesticides, depression and suicide risk in the future in individuals undergoing treatment for depression, attached to the public health service of the city of Anahy/ PR It was developed through the application of four instruments: Beck Scales (Beck Depression Inventory and Beck Hopelessness Scale), Family occupational exposure file to agrochemicals and Instrument for socioeconomic and health profile assessment. The data collection was carried out from March to July 2018, contemplated the stages of user selection through the analysis of the distribution of antidepressants and medical records and interviews. A total of 182 medical records of patients taking antidepressants were analyzed. In these records it was possible to identify 32 subjects with medical diagnosis of depression, over 18 years of age, of whom 28 were interviewed, composing the research sample. As a result, according to the Beck Depression Inventory (BDI), 17.8% (5) subjects with severe depression, 25% (7) with moderate depression, 35.7% (10) with depression mild and 21.4% (6) with minimal depression. According to the Beck Despair Scale (BHS) scores, 21.4% (6) were at risk for suicide in the future. Regarding the variable exposure to agrochemicals, 100% (28) of the individuals had direct or indirect exposure to pesticides, on average for 23 years. The number of people with moderate to severe depression varied significantly among people with different levels of schooling (p = 0.031) and who assessed their health as very poor or good (p = 0.06). Also the number of people at risk for suicide in the future varied significantly among people who self-rated their health as poor or good (p = 0.010). There was no significant change in the number of people with moderate to severe depression and hopelessness regarding the type of exposure to pesticides. However, as all individuals in the sample had direct or indirect exposure to pesticides, and specifically those at risk for suicide in the future had direct exposure to pesticides, there were indications that these variables were related both to the presence of the disorder and to the risk of suicide in the future. The results of this study are intended to provide data for the strengthening of public policies of attention to rural populations exposed to pesticides, to the development of strategies for the prevention of suicidal events and to reinforce the findings of other studies that show the harm of abusive use of agrochemicals for human health.